Gestational loss with normal chromosomes: other possible genetic causes. - Quiroga de Michelena, María Isabel (2015)
Miscarriages without chromosome abnormalities are difficult to deal with. A normal karyotype does not rule out the genetic origin of a pregnancy loss. Mutations of certain genes that intervene in immunologic, coagulation, metabolic and implantation processes among others could cause spontaneous abortions. This review would show the most recent research in these fields. Also, we discuss how perinatal mortality and congenital malformations should be approached in order to obtain an appropriate diagnosis and offer genetic counseling.